MENTAL HEALTH PROBLEMS OF PREGNANT WOMEN, THE CAUSES, AND THE NEED FOR SOCIAL SUPPORT - Tati Nuryati; Yulmaida Amir (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2022)
Some research reports that women who give birth often experience anxiety, fear, and even depression. This study aims to get an overview of mental health problems of pregnant women, the causes, and the need for social support. The study design is a quantitative study with a survey method. Data collection on mental problems for pregnant women begins with early detection for pregnant women by asking 25 simple questions. Data collection uses a questionnaire with a combination of closed and open questions. The location was at the Bojong Menteng Health Center, Rawalumbu, Bekasi City, in the first-second weeks of February 2020. Samples were taken using a population sampling technique with a total of 44 people. Data analysis uses quantitative descriptive methods. The results found pregnant women who experience depression (22.3%), anxiety (43.2%), sleep disorders (70.4%), and psychosomatic disorders. The cause is an unplanned pregnancy, an unwanted pregnancy, financial problems, a less harmonious family, birth spacing, and demands for work. The need for social support from spouses, family, friends, Posyandu cadres in the form of affection, attention, and a place to confide in, also needs support from health workers to assist them in dealing with problems to overcome their perceived complaints. Mental health problems of pregnant women, the causes, and the need for social support must be addressed with the policies and services of mental health services for pregnant women. So that pregnant women can carry out their pregnancy until delivery and the postpartum period is in a healthy and happy state.